Formación docente durante el ejercicio profesional en el cantón San Miguel de Salcedo - Casa Jarrín, Luis Fabián (2017)
The present research work was carried out with the aim of collecting relevant information that helps to the elaboration of transcendental projects in the investigative field of the basic education career at the Technical University of Cotopaxi. For the fulfillment of this project in Salcedo canton was taken as a reference at the Salcedo Educational Unit (UES). It was considered as a main objective to inquire about the teacher training during the professional practice at such educational institution, since it is noticeable that the teacher training on active duty constitutes an important part of the educational establishments, and therefore of the students´ preparation under their tutelage during school hours. At educational level most of the teachers do not continue with their studies after earning their college degree, the accomplishment of the project was seen as a necessity, through the epistemological foundation, the design of instruments, the analysis and discussion of the final results. Relevant information was found for the development of the research work, in different bibliographic sources and with various authors that refer to the project from different points of view, with methods like the analytical and dialectical....